(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This thesis analyses the conceptual differences between economic depreciation and accounting amortization of long-term assets, as well as the conflicts between International Financial Reporting Standards (IFRS) and the Tax Code of the Republic of Uzbekistan in recording these. Based on concrete quantitative evidence, the impact of these differences on enterprise working capital is demonstrated, and the introduction of new analytical accounts into the national chart of accounts is proposed to improve the audit review process.